If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5j + 4 = 2j + 22 Reorder the terms: 4 + 5j = 2j + 22 Reorder the terms: 4 + 5j = 22 + 2j Solving 4 + 5j = 22 + 2j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-2j' to each side of the equation. 4 + 5j + -2j = 22 + 2j + -2j Combine like terms: 5j + -2j = 3j 4 + 3j = 22 + 2j + -2j Combine like terms: 2j + -2j = 0 4 + 3j = 22 + 0 4 + 3j = 22 Add '-4' to each side of the equation. 4 + -4 + 3j = 22 + -4 Combine like terms: 4 + -4 = 0 0 + 3j = 22 + -4 3j = 22 + -4 Combine like terms: 22 + -4 = 18 3j = 18 Divide each side by '3'. j = 6 Simplifying j = 6
| 109-3x=15x+17 | | 2-4=-8 | | -3x-9=5x+15 | | 2t^2-5=6 | | 11-10x=56-45x | | 4x+9=4(x+1) | | 3(x-2)+4(x-4)= | | 6+5k=-6+5k | | 0.12n+0.07(4750-n)=0.08(4750) | | 6y-1=4-y | | 4.7xy-2xz+4xz-12xyz+2zx= | | 4x^2-2x^3=0 | | y^2-5y-2=0 | | 8w-6=8w-6 | | 3(7+10y)=5(6y-6) | | (m+3)(m+3)=18 | | x+3/4=2x-3/4 | | 2*(5a+1)=2*(a+1) | | 2x+8x-1=0 | | 5x=-18x+7 | | 5n-4n+8=9 | | -10=-5p | | 36(51-6.5x)=15(6x-9)+59.4 | | 5(x+6)=x-4 | | 15k-2k-4k=7k+2 | | p-0=89+89 | | 3(x+1)=2x-11 | | 2c+7=4(c-2)-5+3c | | 3(x+19)=2x-11 | | 3k+6-5=7k-10** | | 4x-4=4(x-51) | | 6x+13=3+8x-6 |